Helicobacter pylori infection increases the risk of nonalcoholic fatty liver disease in diabetic population - Chen, Yi; You, Ningning; Shen, Chuchen; Wu, Juju; Zhang, Jinshun (Frontiers in Nutrition, 2023)
Background: The effect of Helicobacter pylori (H. pylori) on nonalcoholic fatty liver disease (NAFLD) in the population is still controversial. Diabetes and NAFLD are both metabolically related diseases, and no studies have classified the population to study the effect of H. pylori on NAFLD in the diabetic population. Methods: A population of people who were examined in the Taizhou Hospital Health Examination Center from 2017-2022 was included, and hematological indicators, body parameters, ultrasound data, and H. pylori detection by urea nitrogen test were collected from patients. All physical examination populations were divided into diabetic and non-diabetic populations. Results: After multivariate logistic regression, H. pylori infection was still a risk factor for NAFLD in diabetic population, but it had no significant effect on NAFLD in non-diabetic population. Moreover, there was a nonlinear correlation between glycosylated hemoglobin and H. pylori infection in diabetic population. In addition, Persistent H. pylori infection increases the incidence of NAFLD in the diabetic population. Conclusion: In the diabetic population, H. pylori infection does increase the risk of developing NAFLD. Glycemic control, as well as eradication of H. pylori infection may have positive implications for reducing the incidence of NAFLD in the diabetic population.